Answer:
Here we do not have the image, but i will try to give a explanation about this type of problem.
When we have the function f(x), the graph of the function h(x) = f(x - x0) means that the graph is displaced by x0 units to the right.
This is because the value of f(x = 0) is equivalent to h( x = x0), but the first one corresponds to the pair (0, f(0)) and the other corresponds to (x0, f(0))
This means that:
g(x) = 3√(x - 4) is displaced 4 units to the right.
g(x) = 3√(x + 4) = g(x) = 3√(x - (-4)) is diplaced 4 units to the left.
g(x) = 3√(x - 1.5) is displaced 1.5 units to the right.
g(x) = 3√(x + 1.5) is displaced 1.5 units to the left.